Synthesis of Poly(methylmethacrylate-co-N-vinyl-2-pyrrolidone) Polymer - Zhu, Chunyang; Wu, Yuanpeng; Singh, Ambrish; Lin, Yuanhua; Liu, Wanying; Deng, Kuanhai (Asian Journal of Chemistry, 2014)
The synthesis of polymer poly(methyl methacrylate-co-N-vinyl-2-pyrrolidone) [P(MMA-co-VP)] from 2-(methoxycarbonyl)-1-propene monomer and N-vinyl-2-pyrrolidone monomer in the presence of potassium peroxidisulfate was done at 75 ºC. The polymerization was refluxed for 6 h under continuous stirring. Nitrogen gas was used to remove the oxygen present in the reflux container during the whole reaction. The polymer was further analyzed using FTIR spectroscopy, X-ray diffraction and nuclear magnetic resonance spectroscopy methods. P(MMA-co-VP) polymer also finds its application as an effective corrosion inhibitor in the presence of CO2 for J55 steel in oil and petroleum industry.